Effects of the sustainable forestry initiative on the quality, abundance, and configuration of wildlife habitats - Azevedo, João (2009)
We analyzed the effects of landscape measures within the Sustainable Forestry Initiative (SFI) program on the suitability, abundance and spatial pattern of vertebrate habitats based on modeling and simulation of landscape and stand structure in a forested watershed in East Texas. Eight vertebrate species representing guilds established according to breeding and foraging requirements were selected: American beaver (Castor canadensis), American woodcock (Scolopax minor), pine warbler (Dendroica pinus), downy woodpecker (Picoides pubescens), barred owl (Strix varia), wild turkey (Meleagris gallopavo silvestris),fox squirrel (Sciurus niger) and gray squirrel (Sciurus carolinensis). Habitat suitability of the landscape in general increased with the implementation of SFI measures and habitat conditions were more diverse and even. Fragmentation and establishment of narrow and elongated habitat areas in a network configuration were the main consequences of the implementation of SFI measures in terms of habitat spatial structure. These changes were usually not limiting for the species analyzed. Mature pine and hardwood stands were absent from the simulated landscapes limiting the habitat for species like downy woodpecker or barred owl.Most of the species considered in this work benefited particularly from the implementation of streamside management zones (SMZs).